Optimal transmission ranges and code rates for frequency-hop packet radio networks. - Subbarao, M.W (IEEE Transactions on communications)
We consider a frequency-hopping multihop packet radio network using M-ary frequency-shift keying modulation in a Rayleigh fading environment. Each node transmits packets using an extended (n, k) Reed-Solomon code and the slotted ALOHA channel access protocol. For this network, we determine the optimum transmission range, optimum code rate, and optimum slotted ALOHA transmission probability to be used by each node in the network. Tradeoffs in choosing the transmission range and code rate, and the spectral efficiency of the network are captured in a new performance measure, information efficiency, which is analogous to expected forward progress. Maximizing the information efficiency yields the optimum desired network parameters